2021
DOI: 10.3389/fendo.2021.675525
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Hypogonadism in Male Patients With Latent Autoimmune Diabetes and Classic Type 2 Diabetes

Abstract: ObjectivesThis study aimed to compare the prevalence of hypogonadism between male patients with latent autoimmune diabetes (LADA) and type 2 diabetes (T2DM) and investigate the risk factors for hypogonadism in these patients.MethodsThis cross-sectional study evaluated 367 male patients with LADA (n=73) and T2DM (n=294) who visited the endocrinology department of Shanghai Tenth People’s Hospital between January 2016 and October 2019 for diabetes management. Sex hormones, lipid profiles, sex hormone-binding glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…In addition, a Chinese study showed that the rate of hypogonadism in the LADA and T2D groups were 8.2%, and 21.7%, respectively (p = 0.017). After adjusting for possible confounders, the rate of hypogonadism in the LADA group was comparable to those of the T2D group ( 64 ).…”
Section: Clinical Manifestations Of Lada In Chinamentioning
confidence: 74%
“…In addition, a Chinese study showed that the rate of hypogonadism in the LADA and T2D groups were 8.2%, and 21.7%, respectively (p = 0.017). After adjusting for possible confounders, the rate of hypogonadism in the LADA group was comparable to those of the T2D group ( 64 ).…”
Section: Clinical Manifestations Of Lada In Chinamentioning
confidence: 74%
“…Tương đồng với nghiên cứu Meili Cai (2021) nồng độ testosterone trung bình ở BN nguy cơ mắc đái tháo đường là 6,1± 2,2 nmol/l, nhóm BN mắc đái tháo đường 4,0 ± 1,9 nmol/l. Thấp hơn nghiên cứu M. Huijben (2023) trên 153 BN nồng độ testosterone trung bình là 8,8 ± 3,2 mmol/l [7]. Nghiên cứu chúng tôi ghi nhận nhóm BN có mức độ rối loạn cương dương (RLCD) nặng, trung bình, nhẹ, không có nồng độ testosterone lần lượt là 7,82; 7,19; 6,23; 5,71 nmol/L, nhóm BN có nồng độ testosterone càng thấp thì mức độ RLCD càng nặng sự khác biệt chưa có ý nghĩa thống kê p< 0,05.…”
Section: Bàn Luậnunclassified
“…A body of evidence from studies in human male subjects [1][2][3] and animal models [4] suggests that low blood testosterone levels may induce insulin resistance and type 2 diabetes mellitus. Possible causality may also go in the opposite direction, since research data also indicate that hyperglycemia may lead to hypogonadism in males [5,6]. From a physiological perspective, this bidirectional relationship between testosterone insufficiency and dysglycemia is complex and largely unknown.…”
Section: Introductionmentioning
confidence: 99%